National trends and survival outcomes of penile squamous cell carcinoma based on human papillomavirus status. (10th October 2021) - Chipollini, Juan; Pollock, Grant; Hsu, Chiu‐Hsieh; Batai, Ken; Recio‐Boiles, Alejandro; Lee, Benjamin R.
Abstract: Background: There are no series evaluating penile squamous cell carcinoma (pSCC) based on human papillomavirus (HPV) infection. Herein, we present national registry data on clinical and survival outcomes for pSCC based on HPV status. Methods: We performed a retrospective review of 1224 pSCC patients with known HPV staining from the National Cancer Database. Patients with cM1 disease, those who did not receive treatment, or had missing follow‐up data were excluded. Logistic regression identified factors associated with locally aggressive disease. Univariable, multivariable, and inverse probability of treatment weighting (IPTW)‐Cox proportional hazard modeling were used to assess hazard ratios (HR) associated with overall survival (OS). Results: After exclusion criteria, we identified 825 cases of which 321 (38.9%) were HPV positive. The HPV‐positivity rate did not significantly change by year. HPV‐positive patients were younger, had lower Charlson‐Deyo performance score, and resided in areas with both lower median household income and lower school education completion. HPV‐positive tumors presented with lower American Joint Committee on Cancer clinical T‐stage (cT), poorer differentiation, lower rates of lymphovascular invasion (LVI), but more node‐positive disease (cN+). For those who underwent lymph node surgery, there were no differences in final pathologic stage, upstaging, or presence of extranodal extension. Only tumor differentiation, LVI, and performance score were independent predictors for locally aggressive disease. HPV status was not a predictor of OS (IPTW‐HR:0.89, p = 0.13). Conclusions: In the largest series evaluating pSCC based on HPV status, HPV‐positive tumors were associated with lower cT stages, less LVI, but more cN + disease. More studies on prognostic factors are needed, and time may still be immature to use HPV information for risk stratification. Abstract : Infection with human papillomavirus (HPV) is endemic and a causative agent for several malignancies in both male and female populations. In this study, we queried a large, cancer registry to look for clinical and survival differences between HPV‐positive versus negative penile tumors. Our results noted a lack of prognostic impact for HPV‐derived tumors, although more studies will be required to validate results.